EXPERIENCE REPLACEMENT DRUGS OF VALPROIC ACID IN CHILDREN OUTPATIENT CLINIC - I. O. Schederkina; N. N. Zavadenko; I. E. Koltunov (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: the article presents the clinical observation of outpatients with a diagnosis of epilepsy in the children’s neurological department Morozovsky Children Hospital translation from the original on generic drug valproic acid. Such changes in anticonvulsant therapy in patients quarter led to a deterioration of the disease in the form of clinical remission failure, impairment at lectroencephalography, as well as the emergence of side effects from the gastrointestinal tract and deterioration of cognitive functions. On the basis of this observation can be confirmed by the fact that patients with epilepsyin remission is not recommended translated from the original drug to a generic.